POLA HUNIAN TEMPAT TINGGAL MASYARAKAT TENGGER DESA WONOKITRI KABUPATEN PASURUAN (The Dwelling Pattem of Tengger Community at Wonokitri Village of Pasuruan District) - Dianing Primanita Ayuninggar; Antariksa Antariksa; Dian Kusuma Wardhani (Unika Soegijapranata Semarang, 2012)
The objectives of this study were to identify and analyze the characteristics of dwelling pattems of Tengger Community at Wonokitri village. The method applied was deSCriptive. The results of the study show that the spatial structure of the traditional houses at Wonokitri village are based on Tenger's adat or customary regulation on division of space that is called the seven po. The house functioning as a home stay that Is designated for tourists there are some additional spaces that Is not In accordance with the seven po concept anymore. The spatial structure of a home stay usually form front-back and left-right pattems that is based on the function and utilization of the spaces. In the traditional houses of Tengger community at Wonokitri village the hierarchical division of the space is based on the sacred and profane criteria defined by philosophy of Tengger's adat or customs about the Lord of the house. There are two pattems of house facing orientation towards the roads, that is North-South orientation and East-West one whereas most of the houses are facing to the west. Tengger's adat or customs philosophy is also applied in the pattem of buildings arrangement design. This can be seen from the absence of house fence beside the existing spatial distance pattem between houses, the pattems of the front yard and side yard, as well as the pattem of putting the side entrance doors.